Propofol protects against high glucose-mediated endothelial injury via inhibition of COX2 and iNOS expressions - Shao Jiayun; Ding Juan; Lu Lihong; Hou Wenting; Wang Fei; Sun Zhirong; Jiang Hui; Zhao Yanjun (Acta Biochimica et Biophysica Sinica)
Perioperative hyperglycemia is a common metabolic disorder in the clinic. Hyperglycemia, via upregulation of E74-like ETS transcription factor 3 (ELF3), induces cyclooxygenase 2 (COX2) and inducible nitric oxide synthase (iNOS) expressions, thus leading to endothelial apoptosis and vascular endothelial injury. Propofol is a widely used anesthetic. In the present study, we explored whether and how propofol protects against high glucose-induced COX2 and iNOS expressions in human umbilical vein endothelial cells (HUVECs). We found that high glucose level decreases cell viability and increases COX2 and iNOS expressions in HUVECs. Our data also indicated that ELF3 overexpression participates in high glucose-mediated cell viability reduction and high glucose-induced COX2 and iNOS expressions. Moreover, propofol treatment improves high glucose-mediated reduction in cell viability and decreases COX2 and iNOS expressions via inhibition of ELF3 expressions. Furthermore, specificity protein 1 (SP1) was found to regulate ELF3 expression, thus mediating endothelial injury. Propofol inhibits high glucose-induced SP1 expression. High glucose increases the abundance of SP1 bound to the ELF3 promoter, which can be reversed by propofol treatment. The protective effect of propofol is reversed by SP1 overexpression. In conclusion, propofol downregulates high glucose-induced SP1 expression, thus attenuating high glucose-induced ELF3 expression, inhibiting high glucose-induced COX2 and iNOS expressions, and improving high glucose-mediated cell viability reduction in HUVECs.